Tiongkok - Sri Lanka: Analisis Dampak Kehadiran Tiongkok di Sri Lanka - Ellya Yunita Aslam; Reni Windiani; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The civil war that occurred between etnic Sinhala and ethnic Tamil in Sri Lanka provided an opportunity for China to be present by using foreign aid instrument. The expansion of foreign aid from China through foreign loans aims to support Sri Lanka in building its infrastructure development. The Chinese foreign loans every year gives Sri Lanka a tendency to experience a condition of dependence. Therefore, this study focuses on analyzing Sri Lanka’s dependence on China and how the impact as a result of this dependence relations. This study analyzes using dependency theory combined with the concept of foreign aid and uses qualitative methods. The results of this study indicate that there is a condition of Sri Lanka’s dependence on China with China’s success in expanding its economic influence in Sri Lanka.